Խոզերի մետաստրոնգիլյոզի տարածվածությունը Հայաստանի Հանրապետությունում - Գրիգորյան, Վալերի; Ղազարյան, Արմինե; Երիբեկյան, Սպարտակ; Գրիգորյան Լիանա (ՀԱԱՀ հիմնադրամ)
В статье представлены результаты исследования распространенности метастронгилеза сви-ней в Армении. Метастронгилез свиней – заболевание, получившее широкое распространение в северо-вос-точной горно-лесной зоне Республики Армения. Из двух распространенных видов патогенов – M. pudendotectusи M. Elongates – M. pudendotectus имеет наиболее обширный ареал. Молодняк примерно в два раза более вос-приимчив к этому заболеванию, чем взрослые особи. По сравнению с другими зонами, в лесной зоне животные болеют чаще, что связано с преобладанием здесь промежуточных хозяев – дождевых червей. Высокий процент заболеваемости отмечается осенью, весной, а наименьшее количество случаев регистрируется зимой․ Pig breeding is a well-established branch of animal husbandry with significant economic and productive po-tential. Due to key biological attributes - such as early sexual maturity, short gestation period, high prolificacy, rapid growth rates, efficient feed conversion, and favorable carcass yield - pig farming holds a leading position in global meat production. The objective of this study was to assess the prevalence of metastrongylosis in domestic pigs (Sus scrofa domesticus) in the Republic of Armenia. The results indicate that porcine metastrongylosis is among the most widespread parasitic respiratory diseases, both globally and within the mountainous forest regions of northeastern Armenia. The predominant etiological agents identified were Metastrongylus pudendotectus and Metastrongylus elongatus, with M. pudendotectus being the most prevalent species. Young pigs (weaners and growers) were found to be approximately twice as susceptible to infection compared to adult swine. Hematological analyses revealed a decrease in erythrocyte count, platelet levels, and hemoglobin concentration in infected animals, accompanied by a marked leukocytosis - indicative of an inflammatory response to parasitic infection. The distribution of the disease strongly correlates with the presence of intermediate hosts, primarily earthworms (Lumbricidae spp.), which are more abundant in forested areas. Consequently, pigs in these ecolog-ical zones exhibit a higher incidence of infection. Seasonality was also observed, with the highest occurrence reported in autumn, followed by spring, and the lowest incidence noted during winter months.
Keywords: Անասնաբուժական բժշկագիտություն և անասնաբուծություն